Low take-up and financial inclusion: Experimental evidence from Argentina's cash transfers - Cruces, Guillermo Antonio (2020)
Cash transfer and other social protection programs have greatly expanded in developing countries in the last two decades, but their coverage varies greatly, even among eligible individuals. We studied the low take-up of benefits by means of a field experiment involving 400,000 beneficiaries of Argentina's largest conditional cash-transfer program (with 2.2 million beneficiaries who are the parents of four million children, 40% of the country?s 0-17 year olds). Beneficiaries are assigned a bank account and a debit card. By using their debit card to spend the allowance, rather than withdrawing cash from ATMs, they can receive a rebate of 15% of their expenditures. However, they systematically fail to claim this benefit: only about 25% of beneficiaries receive this transfer. Our experiment provided information about the effectiveness of an information campaign conducted via text messages or through on-screen messages at ATM machines. The campaign increased take-up (i.e., purchases with debit cards and subsequent rebates) significantly but not substantially. The results indicated that the benefit had low salience, that beneficiaries lacked information about the debit-card program, that frictions existed related to financial inclusion and lack of infrastructure, and that limited information and salience were important but second-order factors.